Genome-wide association analyses identify 143 risk variants and putative regulatory mechanisms for type 2 diabetes - Angli Xue (Nature Portfolio, 2018)
GWAS have so far identified 129 loci associated with type 2 diabetes (T2D). Here, the authors meta-analyse three large T2D GWA studies which uncovers 42 additional loci, further prioritize 33 functional genes using eQTL and mQTL data and propose regulatory mechanisms for three putative T2D genes.